Implikatur percakapan khusus karakter utama dalam animasi manga toon "The Journey" berdasarkan sudut pandang Gazdar - Jambak, Mellinda Raswari; Hasanah, Ummi; Munawwarah, Madinatul (Maliki Interdisciplinary Journal, 2024)
The writing of this article aims to: (1) describe the form of special implicature in "The Journey" animation based on Gazdar’s perspective; and (2) reveal the special implicature in "The Journey" animation based on Gazdar’s perspective. This research is a qualitative research. The primary data source in this research is the anime "The Journey" produced by Manga Toon, while the secondary sources are related journals and books. The data collection techniques used are watching technique, listening technique, and note-taking technique. The results obtained from this study are that there are five forms of special implicature in the animation "The Journey" produced by Manga Toon and Toei Animation based on Gazdar’s perspective (2) the functions of special implicature in the anime "The Journey" produced by Manga Toon based on Gardar’s perspective include (a) to provide facts in language, to provide a more in-depth explanation; (b) namely to connect communication, to explain the use of facts in language.